2016
DOI: 10.5588/ijtld.16.0200
|View full text |Cite
|
Sign up to set email alerts
|

Higher cost of implementing Xpert<SUP>®</SUP> MTB/RIF in Ugandan peripheral settings: implications for cost-effectiveness

Abstract: SUMMARY Setting Initial cost-effectiveness evaluations of Xpert MTB/RIF (Xpert) for tuberculosis (TB) diagnosis have not fully accounted for realities of implementation in peripheral settings. Objective We evaluated costs and diagnostic outcomes of Xpert testing implemented at various healthcare levels in Uganda. Design We collected empirical cost data from five health centers utilizing Xpert for TB diagnosis, employing an ingredients approach. We reviewed laboratory and patient records to assess outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 26 publications
2
30
4
1
Order By: Relevance
“…Our scenario analysis result also revealed that the cost of both diagnostic algorithms was reduced from the base case estimate by increasing the volume of tests per day. This cost estimate is in line with nding from sub-Sahara Africa [29] and Uganda [30] on the cost and cost-effectiveness of the GeneXpert diagnostic test. The cost of the test method was high in health facilities where their testing volume was low.…”
Section: Discussionsupporting
confidence: 82%
“…Our scenario analysis result also revealed that the cost of both diagnostic algorithms was reduced from the base case estimate by increasing the volume of tests per day. This cost estimate is in line with nding from sub-Sahara Africa [29] and Uganda [30] on the cost and cost-effectiveness of the GeneXpert diagnostic test. The cost of the test method was high in health facilities where their testing volume was low.…”
Section: Discussionsupporting
confidence: 82%
“…Few studies have estimated the economic effect of implementing Xpert at the point of care 22,25,26 and all have used modelling analyses rather than prospectively obtained trial data to assess cost-effectiveness. 19,20,24,25,35 In most of these modelling studies, Xpert was cost-effective either as a full replacement 19,24,25,35 or in conjunction with other diagnostic tests 20,21 compared with the standard of care (smearmicroscopy).…”
Section: Discussionmentioning
confidence: 99%
“…9,17,18 Thus, crucial questions for policy makers, and of prime importance to resource allocation planning, are (1) how does the cost of Xpert performed by a minimally trained nurse at point of care compare with when performed by a trained technician at a centralised laboratory; and (2) is point-ofcare placement of Xpert cost-effective? Although multiple studies 17,[19][20][21][22][23][24][25][26] have examined the economic implications of using Xpert in endemic settings, few have focused on the costs or cost-effectiveness when deployed at point of care, 22,25,26 and no studies have calculated cost-effectiveness using clinical outcome data obtained from a pragmatic real-world prospective study. [19][20][21][22]24,25 To address these questions, we analysed prospectively collected cost and clinical outcome data from a large randomised control parent trial that recruited patients from primary care clinics in four southern African countries (South Africa, Zambia, Zimbabwe, Tanzania).…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing efforts in scaling up new rapid diagnostics for tuberculosis involves significant investments in the health systems [ 31 – 34 ]. Major threat which may undermine the impact of these investments is sub-optimal uptake and low test volumes have already been reported from several settings globally [ 33 , 35 , 36 ]. These efforts need to be complemented with proactive outreach and education efforts to ensure provider engagement to ensure provider-literacy and awareness, for maximizing impact of this scale-up.…”
Section: Discussionmentioning
confidence: 99%